Pendampingan Pengelolaan dan Pelestarian Sungai Melalui Program Sekardadu (Sekolah Rawat Daerah Aliran Sungai) di Desa Grogol – Giri – Banyuwangi - Badrul Munif; Muhammad Al Amin; Roudlotun Nurul Laili; Sholihin Sholihin; Akhmad Yanuar Fahmi Pamungkas; Muhammad Nashir; Ivan Rachmawan; Erik Toga; Dian Roshanti (BADAN PENERBIT STIEPARI PRESS, 2022)
The river is one of the sources to meet the water needs of the community. Many residents still depend on the surrounding rivers for clean water for their daily needs. But ironically, the society’s concern for the cleanliness of the river has not yet grown. The low society awareness of environmental conservation in watersheds causes water pollution and water quality to be disturbed. The purpose of this service activity is to provide assistance in river management and conservation through the Sekardadu (Watershed Care School) program in Grogol Village – Giri – Banyuwangi. The method used was in the form of socialization/providing education and assistance by engaging directly with the community in conserving the river. The results of this activity were the community can implement the theory that has been given during socialization, they understands the importance of managing rivers, the emergence of society awareness and understanding to maintain river cleanliness, as well as the growth of shame culture when disposing of garbage, waste, defecation and polluting rivers so that water quality in the river is maintained thus providing great benefits for the continuity of daily life.